THE TEACHERS’ PERCEPTION ON ONLINE ENGLISH LEARNING USING WHATSAPP AT JUNIOR HIGH SCHOOLS IN SEMPU, SUB-DISTRICT - -, Tri Mulyati; Asitatul Hasanah; Nur Hasibin (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2024)
The purpose of the research is to determine the teachers’perceptions on online English learning using WhatsApp. The research method used in this research is descriptive quantitative research. The respondents were 10 English teachers at Junior High Schools in Sempu Sub-District. The sampling technique used was the purposive sampling. The data was collected by using the questionnaire through Google Form and interviews. The result of this research regarding the Teachers’ Perception on Online English Learning Using Whatsapp at Junior High Schools in Sempu, Sub-District is in a good category with overall percentage 60,3%. For the results of interviews, the online English learning using WhatsApp can help them to do an online learning process easily. However, there are still some challenges that happened to online learning using WhatsApp. The monitoring carried out by the teachers on their students was not as easy as face-to-face learning activities. The researcher suggests for the English teachers to use WhatsApp as a learning media. Through WhatsApp, English teachers can deliver the materials easily and creatively.